Anti‐obesity and metabolic efficacy of the β3‐adrenergic agonist, CL316243, in mice at thermoneutrality compared to 22°C. (5th June 2015) - Xiao, Cuiying; Goldgof, Margalit; Gavrilova, Oksana; Reitman, Marc L.
<x xml:space="preserve">Abstract</x> Objective Mice are typically housed at environmental temperatures below thermoneutrality, whereas humans live near thermoneutrality. This difference affects energy physiology and, potentially, anti‐obesity drug efficacy. Here β3‐adrenergic agonist treatment at thermoneutrality (30°C) versus room temperature (22°C) is compared. Methods Male C57BL/6J mice were singly housed at 30°C or 22°C and treated with vehicle or CL316243, a β3‐agonist, for 4 weeks. Food intake, energy expenditure, body and adipose weight, brown adipose activity, white adipose browning, and glucose tolerance were evaluated. CL316243 treatment was studied in both chow‐ and high‐fat diet‐fed mice. Results Mice at 30°C, compared to 22°C, had reduced food intake, metabolic rate, and brown adipose activity, as well as increased adiposity. At both temperatures, CL316243 treatment increased brown adipose activation and energy expenditure and improved glucose tolerance. At 30°C, CL316243 increased energy expenditure disproportionately to changes in food intake, thus reducing adiposity, while at 22°C these changes were matched, yielding unchanged adiposity. Conclusions CL316243 treatment can have beneficial metabolic effects in the absence of adiposity changes. In addition, the interaction between environmental temperature and CL316243 treatment is different from the interaction between environmental temperature and 2, 4‐dinitrophenol treatment reported previously, suggesting that each drug mechanism must be examined to understand the effect of environmental temperature on drug efficacy.